The ameliorative effect of bloodletting puncture at hand twelve Jing-well points on cerebral edema induced by permanent middle cerebral ischemia via protecting the tight junctions of the blood-brain barrier - Nannan Yu; Zhenguo Wang; Yucen Chen; Juntao Yang; Xuan Lu; Yi Guo; Zelin Chen; Zhifang Xu (BMC, 2017)
Abstract Background Cerebral edema, erupting simultaneously with severe ischemic stroke, might lead to increased intracranial pressure, cerebral herniation, and ultimately death. Studies conducted previously by our team have demonstrated the fact that bloodletting puncture at hand twelve Jing-well points (HTWP) could alleviate cerebral edema, which mainly results from the disruption of blood-brain barrier (BBB). The study, therefore, was first designed to demonstrate whether BBB-protection serves an important role in the edema-relief effect of HTWP bloodletting, based on which to research the molecular mechanism underlying. Methods The rats were made into model suffering from permanent middle cerebral artery occlusion (pMCAO) and then bloodletting puncture were treated at HTWP once a day. Wet and dry weight method was adopted to evaluate the degree of brain edema, evans blue extravasation and electron microscopy were used to evaluate the integrity of the BBB, and RT-qPCR was carried out to analyze the expression level of occludin, claudin-5, ICAM-1, and VEGF. Results Results revealed that bloodletting puncture treatment could reduce water content of brain and the permeability of BBB caused by ischemic stroke. In bloodletting puncture group, ameliorated tight junctions could be observed under electron microscopy. It was demonstrated in further study that, in bloodletting group, compared with pMCAO one, the expression levels of occludin and claudin-5 were up-regulated, while ICAM-1 and VEGF were down-regulated. Conclusions In conclusion, bloodletting puncture at HTWP might play a significant role in protecting the tight junctions of BBB, thus alleviating cerebral edema induced by ischemic stroke. Therefore, the therapy of bloodletting puncture at HTWP may be a promising strategy for acute ischemic stroke in the future.